Effective Performance Management Strategies in Facing the VUCA Era - Hosnaidah; Mochammad Isa Anshori (SAJMR : Southeast Asian Journal of Management and Research, 2024)
This research aims to show how effective performance management strategies are in facing the VUCA era. The data of this research was collected through literature study and data analysis from various materials related to performance management in the VUCA era, such as books, journals, and websites, and then examined descriptively. The findings of this study indicate that performance management strategies are adaptive, data-driven, and innovation-oriented. With a focus on agility, use of data, simplification of processes, clarity of communication, development of a culture of innovation, and continuous evaluation, organizations can manage performance more effectively and remain competitive amidst uncertainty and rapid change.